2005
DOI: 10.1029/2004ja010587
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of energetic particle radiation in the close Martian environment

Abstract: [1] Intense, prolonged solar flare activity during March 1989 was used to provide a retrospective scenario for predictions of associated interplanetary shocks and accompanying particle radiation at planet Mars. Shocks from five major flares were simulated to hit both the Earth and Mars during the interval 9-23 March 1989. The simulated scenario was provided by the Hakamada-Akasofu-Fry version 2 (HAFv.2) solar wind model. Since part of the generally required inputs for the model (specifically metric radio Type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…According to Cliver et al (1990), the solar flare associated with the first SSC of this storm event was identified as the March 10 X4.5/3B flare, which is in the top row of Table 1. McKenna-Lawlor et al (2005) also calculated an interplanetary shock propagation by using the HAFv2 model with the solar origin of the X4 flare on March 10 and the first SSC of the storm on March 13-14. The transit time from the occurrence of the solar flare to the first SSC in this event has been estimated to be 54.8 h, which is 3.8 times longer than the event on that occurred on August 4, 1972, with a transit time of 14.6 h (Cliver et al 1990).…”
Section: Overview Of the March 13-14 1989 Storm Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Cliver et al (1990), the solar flare associated with the first SSC of this storm event was identified as the March 10 X4.5/3B flare, which is in the top row of Table 1. McKenna-Lawlor et al (2005) also calculated an interplanetary shock propagation by using the HAFv2 model with the solar origin of the X4 flare on March 10 and the first SSC of the storm on March 13-14. The transit time from the occurrence of the solar flare to the first SSC in this event has been estimated to be 54.8 h, which is 3.8 times longer than the event on that occurred on August 4, 1972, with a transit time of 14.6 h (Cliver et al 1990).…”
Section: Overview Of the March 13-14 1989 Storm Eventmentioning
confidence: 99%
“…For example, an extreme storm that occurred on March 13-14, 1989, which is the focus of this paper, had no solar wind coverage during its onset, main phase, and most of the recovery phase. Therefore, McKenna-Lawlor et al (2005) attempted to reconstruct the interplanetary shocks from five major flares hitting both Earth and Mars during the March 9-23, 1989, by using the HakamadaAkasofu-Fry version 2 (HAFv.2) solar wind model (Fry et al 2001(Fry et al , 2003. Other papers have reconstructed solar wind parameters during large storms by using geomagnetic variations or indices (e.g., Li et al 2006;Cliver et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively unmagnetized bodies such as Mars do not possess a coherent magnetosphere and thus their ionospheres are relatively unshielded from space weather events, which likely lead to interactions deeper in the atmosphere than for magnetized bodies Leblanc et al, 2002]. Previous work examining the impact of solar events at Mars includes characterization of shocks associated with large flares in March of 1989 using data from Phobos-2 [Aran et al, 2007;McKenna-Lawlor et al, 2005]. More recently, Zeitlin et al [2010] summarized solar particle events and galactic cosmic rays (GCRs) recorded by several instruments on Mars Odyssey between 2002 and 2006.…”
Section: Introductionmentioning
confidence: 99%
“…The timing and spatial properties of SEPs are also of interest, given their propensity to arrive suddenly after the onset of solar events. The impact of extreme space weather at Mars is an area of emerging and active research [Falkenberg et al, 2011a;Falkenberg et al, 2011b;McKenna-Lawlor et al, 2008;McKenna-Lawlor et al, 2005]. Relatively unmagnetized bodies such as Mars do not possess a coherent magnetosphere and thus their ionospheres are relatively unshielded from space weather events, which likely lead to interactions deeper in the atmosphere than for magnetized bodies Leblanc et al, 2002].…”
Section: Introductionmentioning
confidence: 99%
“…For further details see Hakamada and Akasofu (1982), Sun et al (1985) and Fry et al (2001). It is noted that the model has also shown success in predicting shock arrivals at Mars and Venus (McKenna-Lawlor et al, 2005 and this predictive capability is presently being tested using improved statistics.…”
Section: Application Of Hafv2 In An Operational Environmentmentioning
confidence: 99%